COMPREHENSIVE MIDWIFERY CARE FOR MRS. L AT THE INDEPENDENT MIDWIFERY PRACTICE OF MIDWIFE Bd. MAULIDA WINANDA, S.Keb SUBULUSSALAM CITY IN 2026 - Nurul Saprida; Fitriani Bancin; Rahayu Ningsih; Ricca Nophia Amra; Ratnawati Bancin, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are key indicators of a nation's welfare. The Continuity of Care (CoC) approach, or continuous midwifery care from pregnancy, labor, postpartum, newborn, to family planning (KB) services, is essential for the early detection of pathological risks and the reduction of MMR/IMR. Objective: To provide comprehensive and continuous midwifery care using the SOAP documentation midwifery management approach for Mrs. L at PMB Bd. Maulida Winanda, S.Keb, Subulussalam City. Methods: This report utilizes a comprehensive longitudinal case study design, following the subject from the third trimester of pregnancy through contraceptive services. The care was provided from March to June 2026. Data were collected through interviews, physical examinations, direct observation, and documentary studies. Results:Antenatal care (ANC) was provided to Mrs. L, 28 years old, G3P2A0, at 39 weeks and 2 days of gestation, presenting with the physiological complaint of lower back pain. On May 31, 2026, at 23:00 WIB, the mother gave birth spontaneously with an occiput anterior presentation; the infant was born healthy and normal. Postnatal care (PNC) was conducted up to the 20th-day postpartum visit, demonstrating a normal uterine involution process, unpalpable uterine fundal height (TFU), well-approximated perineal wound, and smooth lactation. Neonatal care was well-monitored. At the end of the postpartum period, family planning counseling was provided to determine a contraceptive method suitable for a breastfeeding mother. Conclusion: The implementation of comprehensive midwifery care (Continuity of Care) for Mrs. L was proven to proceed physiologically and effectively in monitoring maternal and infant health as well as preventing complications.